Beyond the Call of Duty: a Qualitative Insights into the Drivers of Teacher Motivation in a High-Achieving School - Setiawan*, Naomi Jeanne; Sandra, Lidia (Universitas Syiah Kuala, 2023)
In the realm of educational advancement, teacher motivation is integral to the pedagogical efficacy and development of future leaders. At Sekolah Cendekia Harapan, where the commitment to an inspiring learning atmosphere is paramount, the impetus behind teacher motivation becomes a focal point for academic excellence. This study explores the intrinsic and extrinsic factors influencing teacher motivation, recognizing its pivotal role in enhancing the quality of instruction and student engagement. It builds on the findings of Sulfemi (2020) and Harahap (2018), which link motivational levels to educational resources and a sense of professional calling, respectively. By delving into how these elements interplay at Sekolah Cendekia Harapan, the research aims to shed light on strategies to bolster teacher motivation. The research use in depth interview method and then analyzed using NVivo. The result shows insights promise to shape policies that not only elevate teaching practices but also align with the evolving demands of exceptional education. Thus, this investigation is a cornerstone for sustainable educational improvement, with the potential to significantly uplift both pedagogical standards and student success within the dynamic landscape of modern education